2013
DOI: 10.1108/02632771311324954
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative design: outdoor environments for veterans with PTSD

Abstract: Purpose -Providing veterans diagnosed with post-traumatic stress disorder (PTSD), their families, and staff opportunities to experience physical and mental restoration in outdoor environments designed based on evidence is important. The purpose of this paper is to explore the relationship between evidence-based collaborative design of outdoor environments and their potential capacity to contribute to a veteran's journey to wellness. Design/methodology/approach -There is no existing precedent in the peer-review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…Some authors do not organize the setting or use a specially designed garden, but rather use existing natural environments as a "place for relief from pain, places to assist the struggle" (Anderson, 2011, p. 55) "and search the psychological benefits of spending time in nature (Krasny et al, 2012, p. 5). Wagenfeld et al (2013) emphasize that a collaborative design process where design outcomes meet specific populations' needs, is needed to further develop the field. Cooper-Marcus and Sachs (2013) mention the need for flexibility in the design of the garden, so it can be changed in relation to the soldiers' needs, whose trauma can be reactivated if the colours, sounds or planting remind them of the war zone.…”
Section: Theme 1 Type Of Interventionsmentioning
confidence: 98%
“…Some authors do not organize the setting or use a specially designed garden, but rather use existing natural environments as a "place for relief from pain, places to assist the struggle" (Anderson, 2011, p. 55) "and search the psychological benefits of spending time in nature (Krasny et al, 2012, p. 5). Wagenfeld et al (2013) emphasize that a collaborative design process where design outcomes meet specific populations' needs, is needed to further develop the field. Cooper-Marcus and Sachs (2013) mention the need for flexibility in the design of the garden, so it can be changed in relation to the soldiers' needs, whose trauma can be reactivated if the colours, sounds or planting remind them of the war zone.…”
Section: Theme 1 Type Of Interventionsmentioning
confidence: 98%
“…Any service-learning experience may prove beneficial to a student veteran participant, but there seems to be something uniquely beneficial about situating the service in an outdoor environment. While being outdoors contributes to positive effects on veterans-particularly those who may struggle with post-traumatic stress (Wagenfield, Roy-Fisher. & Mitchell, 2013)-veterans who participated in just a six-day wilderness experience in Australia showed an "increase in selfreported wellbeing and mental health" following the activity-based program which included opportunities for peer-to-peer interactions (Bird, 2015).…”
Section: Veterans and The Outdoorsmentioning
confidence: 99%
“…Natural lighting, trees, greenery, and green spaces in general, are linked to improved positive health outcomes, and social cohesion (Ekkel & de Vries, ). Wagenfeld, Roy‐Fisher, and Mitchell () found that access to nature, particularly nature areas developed through a collaborative process, improved physical and mental health outcomes for veterans diagnosed with PTSD. Other researchers (e.g., Owens, ; Kaplan & Kaplan, ) have explored the characteristics of natural space that are valued by teenagers and others and that promote restoration and other positive health outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%